Nutritional strategies to optimize performance, training adaptation and recovery in team sports - Flueck, J. L.; Kyburz, S. A. (sems-journal, 2021)
Abstract: Team sports performance is highly demanding in terms of physiological and psychological aspects. Furthermore, the competition schedule is often time constrained and athletes need to travel between games during recovery. Therefore, it seems very important to optimize nutritional strategies around training sessions as well as while traveling or competing. This review discusses a variety of different aspects, which are important in the development of a nutritional strategy in a club. It summarizes how the medical and performance staff of a team can provide the right nutritional strategies to optimize training adaptation and recovery. Furthermore, specific nutritional aspects for female, youth and traveling athletes as well as athletes recovering from injury are discussed. Besides nutritional strategies, teams should be cautious regarding the monitoring of body composition. Choosing the right time point in the season together with selecting a reliable and valid method and measuring under standardized circumstances is essential. Furthermore, athletes need to be educated on the risks and benefits of supplement use. This can reduce the risk of a positive doping test as well as the use of unnecessary, inappropriate and ineffective supplements. Zusammenfassung: Die sportlichen Belastungen im Teamsport sind aus physiologischer und psychologischer Sicht sehr anspruchsvoll. Zudem ist der Wettkampfplan oft dicht gedrängt, und die Athleten müssen zwischen den Spielen reisen und sich gleichzeitig erholen. Daher ist es entscheidend, die Ernährungsstrategien sowohl während des Trainings als auch auf Reisen oder im Wettkampf zu optimieren. Dieser Reviewartikel fasst verschiedene Aspekte zusammen, die für die Entwicklung einer Ernährungsstrategie in einem Club wichtig sind. Zuerst wird zusammengefasst, wie das medizinische und sportwissenschaftliche Team die richtigen Ernährungsstrategien zur Optimierung der Trainingsanpassung und Erholung bereitstellen kann. Ausserdem umfasst er Aspekte zur Ernährung von Sportlerinnen, Jugendlichen und reisenden Sportlern sowie während der Rehabilitation von Verletzungen. Zusätzlich befasst sich der Artikel mit der Analyse der Körperzusammensetzung von Athleten. Die Wahl des richtigen Zeitpunkts der Saison zusammen mit einer zuverlässigen, validen sowie reliablen Methode unter standardisierten Bedingungen ist zentral. Ebenfalls müssen Sportler über das Risiko und den Nutzen der Verwendung von Nahrungsergänzungsmitteln informiert werden. Dies reduziert das Risiko eines positiven Dopingtests, und die Verwendung unangemessener und unwirksamer Supplemente wird vermieden.